(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The concept "innovations" and the maintenance of innovations of the higher education is analyzed in the article. Communication between innovations in business and in education comes to light. The reasons of difficult process of the course of innovative reforms are formulated. The conclusion is: it is need to weighed approach to the happening changes for system of Russian education.